Astronomy with Radioactivities - Diehl, Roland; Hartmann, Dieter H.; Prantzos, Nikos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book introduces the reader to the field of nuclear astrophysics, i.e. the acquisition and reading of measurements on unstable isotopes in different parts of the universe. The authors explain the role of radioactivities in astrophysics, discuss specific sources of cosmic isotopes and in which special regions they can be observed. More specifically, the authors address stars of different types, stellar explosions which terminate stellar evolutions, and other explosions triggered by mass transfers and instabilities in binary stars. They also address nuclear reactions and transport processes in interstellar space, in the contexts of cosmic rays and of chemical evolution. A special chapter is dedicated to the solar system which even provides material samples. The book also contains a description of key tools which astrophysicists employ in those particular studies and a glossary of key terms in astronomy with radioactivities.
Part I The Role of Radioactivities in Astrophysics -- Introduction to Astronomy With Radioactivity -- The Role of Radioactive Isotopes in Astrophysics -- Part II Specific Sources of Cosmic Isotopes -- Radioactivities in Low-and Intermediate-Mass Stars -- Massive Stars and their Supernovae -- Binary Systems and Their Nuclear Explosions -- Part III Special Places to Observe Cosmic Isotopes -- Distributed Radioactivities -- Part IV Tools for the Study of Radioactivities in Astrophysics -- Nuclear Reactions -- Instruments for Observations of Radioactivities -- Part V Epilogue -- Perspectives -- Annotations on Chemical Evolution -- Radionuclides and Their Stellar Origins -- Milestones in the Science of Cosmic Radioactivities -- Glossary: Key Terms in Astronomy With Radioactivities -- Index.
Keywords: Physics; Astronomy; Physics; Astronomy, Astrophysics and Cosmology